Education, skills, and duration of unemployment in Ghana - Ebenezer Gyan Yirenkyi; Godwin Debrah; Kwami Adanu; Edwin Atitsogbui (Cogent Economics & Finance, 2023)
The unmatched growth in available jobs, given the rising youth population, is a major concern for policymakers in sub-Saharan African countries (SSAs), particularly Ghana. The weakness in the link between education and the needed skill by the industry, has been labelled as the cause of rising unemployment and prolonged unemployment duration in Ghana. This paper presents new evidence on the effect of education and skill-language, computer and numeracy skills-on unemployment duration in Ghana using the Skill Towards Employment and Productivity (STEP) skill dataset collected by the World Bank in 2013. The study employs Cox's Proportional Hazard Model to examine the effect of education, language, computer and numeracy skill on unemployment duration. We found that education reduces the duration of unemployment in general. However, the effect is higher for exiting salaried work compared to self-employed jobs. Proficiency in computer, English or Ewe reduces the duration of unemployment. In particular, we observe that individuals highly skilled in computer use are 34.4% more likely to exit unemployment compared to those without computer skills. Interestingly, the effect of computer skills is through channels other than formal education.
Keywords: 330; Ghana; education; hazard ratio; skill; unemployment duration